1991
DOI: 10.1111/j.1745-4557.1991.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characterization of Ketchup

Abstract: Ketchup flow properties were investigated with a concentric cylinder viscometer in the temperature range .from 30°C to 80°C. A partial characterization of the product viscoelastic behavior at 30°C was also made by "Strain test" and "Frequency test. " The Harper and El Sahrigi equation (7" = acJ eEdRT), as well as the equation that links the apparent viscosity of ketchups to the serum viscosity and to the pulp content (% = qserum +A(%PJB), do not describe adequately the ketchup flow behavior that we found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…Both indices as predicted by models were positively and significantly (P < 0.05) affected by the increase in hydrocolloid concentration (Table 3). Similar results for the flow behaviour indices and consistency coefficients have been reported previously by Dervisoglu & Kokini (1986), Rani & Bains (1987), Bottiglieri et al (1991), Sahin & Ozdemir (2004) and Sharoba et al (2005). Singh Gujral et al (2002) also found that the addition of different hydrocolloids increased the consistency of tomato ketchup.…”
Section: Flow Behavioursupporting
confidence: 88%
See 1 more Smart Citation
“…Both indices as predicted by models were positively and significantly (P < 0.05) affected by the increase in hydrocolloid concentration (Table 3). Similar results for the flow behaviour indices and consistency coefficients have been reported previously by Dervisoglu & Kokini (1986), Rani & Bains (1987), Bottiglieri et al (1991), Sahin & Ozdemir (2004) and Sharoba et al (2005). Singh Gujral et al (2002) also found that the addition of different hydrocolloids increased the consistency of tomato ketchup.…”
Section: Flow Behavioursupporting
confidence: 88%
“…Ketchups are time-independent, non-Newtonian fluids that show a small thixotropy (Bottiglieri et al, 1991). Tomato ketchup obtains its viscosity from naturally occurring pectic substances in fruits.…”
Section: Introductionmentioning
confidence: 99%
“…However, Bottiglieri and others () stated that this relation was not adequate to describe the flow properties of tomato ketchup. As can be expected, the rheology of food suspensions is much more complex than that of suspensions of monodisperse, solid spheres.…”
Section: Rheology Of Plant‐tissue‐based Food Suspensionsmentioning
confidence: 99%
“…Ketchup is non-Netwonian, shear-thinning fluid, with yield stress. It also shows thixotropy and viscoelastic properties (Bottliglieri et al 1991;Varela et al 2003;Sahin and Özdemir 2004;Sharoba et al 2005;Koocheki et al 2009). Rheological properties of ketchup are essentially affected by the rheological characteristics of tomato concentrate (Bayod et al 2008; Barbana and El-Omri 2009).…”
Section: Introductionmentioning
confidence: 99%